A dimensão do Atlântico Sul na política externa e na defesa do Brasil, dos anos 70 ao limiar do século XXI - Aquino, Edson Tomaz de (2008)
The main purpose of this work is to show the growing importance of South Atlantic Ocean to Brazil s foreign policy and security issues, from the seventies to 21st century. The oil crises in the early seventies changed brazilian perception about its maritime frontier. The enlargement of territorial sea to 200 miles and a diplomatic approach to Africa were strategic to assure Brazilian interests in the South Atlantic. The central role of Brazil to build the Zone of Peace and Cooperation of the South Atlantic stresses the choice to the multilateralism and the international law. This choice results from regional and hemispheric context. In the early 21st century, the international system allows Brazil to drawn a military capability towards its maritime frontier. Economic resources as great stocks of oil could turn the South Atlantic a vulnerable zone to Brazilian interests. Idealism and Realism on foreign politics and defense issues tend to combine themselves on Brazil s projection at South Atlantic